2016
DOI: 10.1586/1744666x.2016.1152888
|View full text |Cite
|
Sign up to set email alerts
|

The role of Bruton’s tyrosine kinase in autoimmunity and implications for therapy

Abstract: Summary Bruton’s tyrosine kinase (BTK) mediates B cell signaling and is also present in innate immune cells but not T cells. BTK propagates B cell receptor (BCR) responses to antigen-engagement as well as to stimulation via CD40, toll-like receptors (TLRs), Fc receptors (FCRs) and chemokine receptors. Importantly, BTK can modulate signaling, acting as a “rheostat” rather than an “on-off” switch; thus, overexpression leads to autoimmunity while decreased levels improve autoimmune disease outcomes. Autoreactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 132 publications
(138 reference statements)
1
114
0
Order By: Relevance
“…Bruton's tyrosine kinase (BTK) pays a critical role in B-lymphocyte development and in mast cell activation through high-affinity IgE receptors (Crofford et al, 2016). Mutations of BTK are associated with X-linked agammaglobulinemia, which causes immunodeficiency.…”
Section: E Bruton's Tyrosine Kinasementioning
confidence: 99%
“…Bruton's tyrosine kinase (BTK) pays a critical role in B-lymphocyte development and in mast cell activation through high-affinity IgE receptors (Crofford et al, 2016). Mutations of BTK are associated with X-linked agammaglobulinemia, which causes immunodeficiency.…”
Section: E Bruton's Tyrosine Kinasementioning
confidence: 99%
“…Bruton's tyrosine kinase (BTK) is a cytoplasmic tyrosine kinase expressed in cells of hematopoietic origin, including B cells and macrophages, but not T cells. As a member of the Tec kinase family, BTK is a key regulator of B cell receptor (BCR)‐mediated signaling, and plays pivotal roles in B cell development, differentiation, activation, class‐switching, proliferation, survival, and cytokine release . BTK also mediates Fc receptor (FcR) signaling and may have a role in toll‐like receptor signaling in myeloid cells.…”
mentioning
confidence: 99%
“…6,7 This correlates with murine studies regarding the role of Btk in autoimmunity, as we and others have shown that Btk-deficiency protects against multiple forms of autoimmune disease in pre-clinical models. 2,813 Further, we have not found evidence that Btk-deficiency might induce autoimmunity on its own, never having seen spontaneous arthritis either in Btk-deficient C57BL/6 mice, nor on the autoimmune-prone NOD background.…”
Section: Replymentioning
confidence: 64%
“…Btk-deficiency in mice profoundly depletes autoreactive B cells, while normal B cells are less affected. 1,2 This contrasts human patients who lack BTK, in whom all B cell subsets are depleted. These patients have fewer than 1% normal numbers, with failure of humoral immunity known as X-linked agammaglobulinemia (XLA).…”
Section: Replymentioning
confidence: 99%